Correction: Evans et al. Salt Cavern Exergy Storage Capacity Potential of UK Massively Bedded Halites, Using Compressed Air Energy Storage (CAES). Appl. Sci. 2021, 11, 4728 - David Evans; Daniel Parkes; Mark Dooner; Paul Williamson; John Williams; Jonathan Busby; Wei He; Jihong Wang; Seamus Garvey (Applied Sciences, 2022)
The author wishes to make a change to the mail address of Dr [...]